Public Opinion and Criminal Justice Reform - Drakulich, Kevin M. (American journal of criminal justice, 2022)
How can public opinion research help achieve badly needed criminal justice reforms? Unfortunately, public opinion has frequently been used in ways that help construct barriers to reform. Understanding the reasons—the influences on public opinion about crime and justice, the popularity of punitiveness and reform, and the way political actors interpret opinion—for this is important. But there is also promise in public opinion research for achieving a more just system, and public opinion research can also be a tool in elevating structurally marginalized voices, as well as those most impacted by crime and justice processes. Doing so requires a commitment to involving diverse voices inside and outside the academy, as well as a thoughtful and mutually beneficial integration of theory and public opinion research.